KAJIAN SIFAT FISIKA DAN KIMIA TANAH PADA LAHAN KARET DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTP.NUSANTARA III GUNUNG PARA (Study of Physical and Chemical Soil Properties in Rubber Plantation With Several Vegetations That Grow in Gunung Para - Sisca Christine Pratiwi Pardosi; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2017)
ABSTRACT Physical and chemical soil properties are important factors for the growth of rubber plant. This research is aimed to study physical and chemical soil properties on the rubber plant with vegetation such Mucuna bracteata, Nephrolepis biserrata, grass, and without vegetation in Gunung Para PTP.Nusantara III. The observed parameters are soil texture, porosity, water content of field capacity, soil permeability, total nitrogen, avalaible soil phosphate , and land pottasium exchange. The results showed that the soil type was ultisol with sandy clay loam texture and pH ranged from 6.33 to 6.47 (slightly sour). The soil vegetations porosity was 50.43 to 52.24% at 5 cm depth and 48.53 to 48.93% at 25 cm depth, the water content of field capacity was ranged from 40.97 to 44.77%, permeability was ranged from 4.7 to 6.5 cm/h at 5 cm depth and 2.82 to 4.84 cm/h at 25 cm depth, total N was ranged from 0.10 to 0.11%, available P was ranged from 5.6 to 9.98 ppm, K exchange of land was ranged from 0.44 to 0.52 me/100g. The soil without vegetation porosity was 48.73% at 5 cm depth and 46.83 at 25 cm depth, the water content of field capacity was 34.14%, permeability was 2.88 at 5 cm depth and 2.55 at 25 cm depth, total N was 0.009%, avalaible P was 5.5 ppm, K exchange of land was 0.33 me/100g. Keyword: Soil chemistry and physics, vegetation, rubber plantation ABSTRAK Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan karet. Penelitian ini bertujuan untuk mengkaji sifat fisika dan kimia tanah pada lahan karet dengan vegetasi Mucuna bracteata, paku harupat (Nephrolepis biserrata), rumput, dan tanpa vegetasi di kebun PTP.Nusantara III Gunung Para. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabilitas tanah, N-total, P tersedia, dan K-tukar tanah. Hasil penelitian menunjukkan jenis tanah ultisol bertekstur lempung liat berpasir dan pH berkisar 6,33-6,47 (agak masam). Tanah dengan vegetasi mempunyai porositas berkisar 50,43-52,24% pada kedalaman 5 cm dan 48,53-48,93% pada kedalaman 25 cm, kadar air kapasitas lapang berkisar 40,97-44,77%, permeabilitas tanah berkisar 4,7-6,5 cm/jam pada kedalaman 5 cm dan 2,82-4,84 cm/jam pada kedalaman 25 cm, N-total berkisar 0,10-0,11%, P tersedia berkisar 5,6-9,98 ppm, dan K-tukar tanah berkisar 0,44-0,52 me/100g. Tanah tanpa vegetasi mempunyai porositas 48,73% pada kedalaman 5 cm dan 46,83% pada kedalaman 25 cm, kadar air kapasitas lapang 34,14%, permeabilitas tanah 2,88 cm/jam pada kedalaman 5 cm dan 2,55 cm/jam pada kedalaman 25 cm, N-total 0,09%, P tersedia 5,5 ppm, dan K-tukar tanah 0,33 me/100g. Kata Kunci: Fisika dan kimia tanah, vegetasi, lahan karet